Applying Personal Balanced Scorecard (PBSC) Concept in Islamic Education - Iswan,; Herwina,; Hassan, Zainudin; Farihen, (International Journal of Psychosocial Rehabilitation, 2020)
This research was about applying the Personal Balanced Scorecard Concept (PBSC) in Islamic education that was done by using the qualitative method. This research was conducted at MAN 4 Model Jakarta, Indonesia. The research instrument used was a questionnaire, which was conducted for 19 teachers who taught at MAN 4 Model Jakarta, Indonesia, who were considered to be quite representative of the other teachers. The results of this research found that it is proven that Islamic education today, including Islamic-based education, is in the pull of a business paradigm that is transactional, pragmatic, and service-oriented. Those things are used in economic business management at first and applied to manage education by now. The application of management theory, which has a transactional-pragmatic business logic, has problems when used to manage education, which logically builds education with dignity, civilization, and humanity. Education is born from a good system (good planning system) with material and a good governance system (good governance system), which is delivered by good teachers (good teachers) through the components of a good and quality learning process, especially teachers. Application of the Personal Balanced Scorecard (PBSC) theory from Hubert K. Rampersad through the PDAC Cycle approach.